Collapse [videorecording (DVD)] - Ruppert, Michael C.; Smith, Chris, 1970- (Film Buff ; [Distributed by] MPI Media Group, 2010)
Meet Michael Ruppert, a different kind of American. A former Los Angeles police officer turned independent reporter, he predicted the current financial crisis in his self-published newsletter, From the Wilderness, at a time when most Wall Street and Washington analysts were still in denial. Director Chris Smith has shown an affinity for outsiders in films like American Movie and The Yes Men.